Assessment of heavy metal and petroleum hydrocarbon contamination in the Sultanate of Oman with emphasis on harbours, marinas, terminals and ports. Issue 1 (15th August 2017) - Jupp, Barry P.; Fowler, Scott W.; Dobretsov, Sergey; van der Wiele, Henk; Al-Ghafri, Ahmed
Abstract: The assessment here includes data on levels of contaminants (petroleum hydrocarbons and heavy metals) in sediments and biomonitor organisms, including the eulittoral rock oyster Saccostrea cucullata and subtidal biomonitors, the barnacle Balanus trigonus and the antipatharian coral Antipathes sp., at harbours, marinas, terminals and large ports along the coastline of Oman. TBT levels in harbour and port sediments up to a maximum of 100 ppb TBT dry weight are highlighted. Oysters contained concentrations up to 367 ppm mg TPH/kg dry weight. The maximum levels of Cd, Cu, Pb and Zn were found in the subtidal sediments and barnacles at the oil tanker loading Single Buoy Mooring stations in Mina Al Fahal. In general, the levels of most of the contaminants analysed are at low to moderate concentrations compared to those in highly contaminated sites such as shipyards and dry docks, but continued monitoring is recommended especially during any dredging campaigns. Highlights: Port facilities are hot spots of metal and petroleum contamination in Oman. TBT was found in sediments and biomonitors in several ports with a maximum level of 100 ppb. Maximum levels of hazardous metals and petroleum hydrocarbons in sediments were found at the SBMs in Mina Al Fahal. Barnacles at the Mina Al Fahal SBMs contained elevated levels of Cd, Cu, Pb and Zn. Measured contaminants are generally low compared to highly contaminated sites worldwide.